THU0172 Risk for Serious Adverse Events Associated with Oral Corticosteroid Therapy in Patients with Rheumatoid Arthritis: A Uk Population-Based Study. (15th July 2016) - Wilson, J.C.; Sarsour, K.; Gale, S.; Pethö-Schramm, A.; Jick, S.S.; Meier, C.R.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, erosive form of inflammatory arthritis characterized by a distinctive pattern of bone and joint destruction. Along with disease-modifying antirheumatic drugs and newer biologic therapy, treatment can include oral corticosteroids (oCS), predominantly prednisolone or prednisone. CS are associated with a variety of adverse effects. 1 Objectives: Using data from the UK's Clinical Practice Research Datalink, we estimated the incidence rates (IRs) and incidence rate ratios (IRRs) of known oCS-related serious adverse events (SAEs) of interest in an RA cohort and in a non-RA general population (GP) comparison group matched on age, sex, and time. We also explored the role of oCS use on the risk for SAEs of interest by comparing RA patients of varying exposure levels of oCS. Methods: Patients with a first-time diagnosis of RA who were ≥18 years of age were identified and matched to patients in a non-RA GP comparison group of equal size. Group IRs and IRRs were estimated for diabetes, osteoporosis, fractures, glaucoma, hypertension, thrombotic stroke or myocardial infarction (MI), gastrointestinal (GI) perforation or bleeding, and death for the RA group and the GP group. We then performed a series of nested case-control analyses examining the effect of oCS use on the risk for SAEs of interest. We used conditional logistic regression to calculate the unadjusted and multivariate adjusted odds ratios (ORs) with 95% confidence intervals (CIs) for the association between oCS use and the risk for each separate outcome of interest. We stratified the analyses according to increasing cumulative and average daily oCS use. Results: The cohort consisted of 34, 047 RA patients and 34, 047 matched non-RA GP patients. Mean follow-up time was ∼8 years. The incidence for most SAEs was greater in the RA group than in the GP group. IRRs (95% CIs) for SAEs of interest were diabetes (1.21; 1.13–1.31), osteoporosis (2.11; 1.96–2.27), fractures (1.16; 1.08–1.24), glaucoma (1.08; 0.94–1.22), hypertension (1.13; 1.09–1.18), thrombotic stroke or MI (1.22; 1.11–1.34), GI perforation or bleeding (1.3; 1.15–1.47), and death (1.17; 1.11–1.22). In multivariate analyses, increasing risks for diabetes, osteoporosis, fractures, thrombotic stroke or MI, and death were observed with increasing cumulative oCS use ( p <0.05 for trend). RA patients receiving an average daily dose >7.5 mg/day had an increased adjusted OR (95% CI) for diabetes (1.49; 1.21–1.84), osteoporosis (1.41; 1.20–1.66), fractures (1.22; 1.03–1.45), thrombotic stroke or MI (1.61; 1.27–2.04), and death (1.49; 1.27–1.74). Conclusions: Patients with RA experienced an increased incidence of diabetes, osteoporosis, fractures, hypertension, thrombotic stroke or MI, GI perforation or bleeding, and death compared with age- and sex-matched controls. Increasing cumulative oCS doses and average daily oCS doses were associated with increased odds of diabetes, osteoporosis, fractures, thrombotic stroke or MI, and death. References: Venables PJW. Rheumatoid arthritis treatment (beyond the basics). UpToDate, Inc. 2016. http://www.uptodate.com/contents/rheumatoid-arthritis-treatment-beyond-the-basics. Accessed January 21, 2016. Disclosure of Interest: J. Wilson: None declared, K. Sarsour Shareholder of: Roche, Employee of: Roche, S. Gale Shareholder of: Roche, Employee of: Roche, A. Pethö-Schramm Employee of: F. Hoffmann-La Roche, S. Jick: None declared, C. Meier Shareholder of: Hoffmann-La Roche, Grant/research support from: Hoffmann-La Roche